DISTRIBUSI SPASIAL GENANGAN AIR LAUT BERDASARKAN ANALISIS DATA SATELIT ALTIMETRI ENVISAT DI WILAYAH PESISIR BARAT KABUPATEN BULELENG, BALI - I Putu Sriartha; I Wayan Krisna Eka Putra (Environmental Research Center (PPLH) of Udayana University, 2015)
This research was conducted in the western coastal region of Buleleng which includestwo districts, namely: Seririt District and Gerokgak District. The research aims were (1) toanalyze the trend of the dynamics of sea level in the period of 2002 to 2010, and (2) to predictthe spatial distribution of flood of sea water. The data used are Envisat satellite altimetry datafrom the results of post-processing data, which were then analyzed the trend of mean sea leveland forecast of sea level rise for year 2020 using linear regression analysis. To determine thespatial distribution of area flood of sea water, then the data of level rise forecast were analyzedwith Geographic Information System (GIS). The results of this research define that the functionalrelationship of the trend of mean sea level rise in the area of research is y = 0.051 x + 1.612. Theprediction of mean sea level rise that is obtained every year 5.1 cm and for 2020, the sea levelrise is predicted to reach 2,224 cm. The width of coastal area that is potentially flooded of seawater reaches 812.954 m2 (0.227%). Spatially, the widest food area is Pejarakan village and thenarrowest is Celukan Bawang village. The percentages of the villages that are flooded to areavillages show a relatively homogeneousdistribution.